Ictelmis, a new riffle beetle genus from Ecuador (Coleoptera: Elmidae) - Čiampor, Fedor Jr; Linský, Marek; Čiamporová-Zaťovičová, Zuzana (Zootaxa, 2019)
A new minute riffle beetle genus Ictelmis gen. nov. and the type species Ictelmis martae sp. nov. are described from Ecuador. The description is supported by characteristic morphological features and DNA barcoding data, drawings and habitus photographs are provided. Based on molecular data and morphology it is suggested that Ictelmis is closely related with Onychelmis Hinton, and Notelmis Hinton.